Elevated pre-surgical CA15-3: does it predict the short-term disease-free survival of breast cancer patients without distant metastasis? - Mudduwa LKB; Wijayaratne GB; Peiris HH; Gunasekera SN; Abeysiriwardhana D; Liyanage N (Dove Medical Press, 2018)
Lakmini KB Mudduwa,1 Gaya B Wijayaratne,2 Harshini H Peiris,3 Shania N Gunasekera,1 Deepthika Abeysiriwardhana,1 Nimsha Liyanage1 1Department of Pathology, Faculty of Medicine, University of Ruhuna, Galle, Sri Lanka; 2Department of Microbiology, Faculty of Medicine, University of Ruhuna, Galle, Sri Lanka; 3Medical Laboratory Science Degree Program, Faculty of Medicine, University of Ruhuna, Galle, Sri Lanka Background: CA15-3 is the most commonly used tumor marker in breast cancer. Its prognostic role has been described in the metastatic setting, but the role of pre-surgical CA15-3 in the assessment of patients with breast cancer without metastasis has not been substantiated yet. Methodology: From February 2014 for a 2-year period, this prospective study included all patients who were diagnosed with primary breast cancer and underwent surgery at a tertiary care hospital. The serum level of CA15-3 was assessed on a pre-surgical blood sample and later at the 3-, 6-, 9-, and 12-month follow-up by enzyme-linked immunosorbent assay. Disease-free survival (DFS) was analyzed with a Kaplan–Meier model and log-rank test. Results: We enrolled 195 patients (mean age ± SD 57.84 years ±13.819, range, 28–95) with breast cancer. The prevalence of elevated (≥30 U/mL) pre-surgical CA15-3 was 35.9%, and it reduced to 14.3% at 3 months after mastectomy. Pre-surgical CA15-3 had a significant association only with the size of the tumor (p=0.047). Patients who did not have elevated pre-surgical CA15-3 (≥30 U/mL) had the best short-term DFS, and it was worst when the pre-surgical CA15-3 was >100 U/mL (p=0.041). Conclusion: Elevated pre-surgical CA15-3 is a predictor of poor short-term DFS of patients with breast cancer without distant metastasis. Keywords: breast cancer, pre-surgical CA15-3, short-term disease-free survival, prognosis